Assessment of the potential climate change on rice yield in lower Ayeyarwady Delta of Myanmar using EPIC model - Naw Mar Lar (2019)
© 2018, Faculty of Environment and Resource Studies,Mahidol University. All rights reserved. Climate change has been occurring and its consequences are a threat to rice production and hence food security. In this study, the effect of climate change on rice yield has been assessed by using the Environmental Policy Integrated Climate model under climate change scenarios RCP4.5 (medium emissions) and RCP8.5 (high emissions) and to propose alternative adaptive measures for farmers’ livelihoods in the lower Ayeyarwady Delta. The results show that the average yield increase of early rice are 11.84% and 7.56% and the average yield reduction of late rice are 37.37% and 50.89% under both scenarios. The study found that rice yield reduction will be significantly higher under the RCP8.5 than that of RCP4.5 for both rice. Yield reductions are attributed to increases in mean maximum and minimum temperatures and variation in rainfall pattern. The model result suggests that changing the sowing date is a good option for compensating the future rice yield reduction. The other adaptations that offset the rice yield response to climate change include providing farming machines, irrigation facilities, improving infrastructure, improvement in cultivars that resist disease, pest and drought, better weather forecast and extension systems.